A community‐led design for an Indigenous Model of Mental Health Care for Indigenous people with depressive disorders. (7th June 2021) - Farah Nasir, Bushra; Brennan‐Olsen, Sharon; Gill, Neeraj S; Beccaria, Gavin; Kisely, Steve; Hides, Leanne; Kondalsamy‐Chennakesavan, Srinivas; Nicholson, Geoffrey; Toombs, Maree
Abstract: Objective : To generate outcomes for the development of a culturally appropriate mental health treatment model for Indigenous Australians with depression. Methods : Three focus group sessions and two semi‐structured interviews were undertaken over six months across regional and rural locations in South West Queensland. Data were transcribed verbatim and coded using manual thematic analyses. Transcripts were thematically analysed and substantiated. Findings were presented back to participants for authenticity and verification. Results : Three focus group discussions (n=24), and two interviews with Elders (n=2) were conducted, from which six themes were generated. The most common themes from the focus groups included Indigenous autonomy, wellbeing and identity. The three most common themes from the Elder interviews included culture retention and connection to Country, cultural spiritual beliefs embedded in the mental health system, and autonomy over funding decisions. Conclusions : A treatment model for depression must include concepts of Indigenous autonomy, identity and wellbeing. Further, treatment approaches need to incorporate Indigenous social and emotional wellbeing concepts alongside clinical treatment approaches. Implications for public health : Any systematic approach to address the social and cultural wellbeing of Indigenous peoples must have a community‐led design and delivery.